Activating embryonic development in Drosophila. - Avilés-Pagán, E.E.; Orr-Weaver, T.L. (Seminars in cell and developmental biology, 2018)
The transition from oocyte to embryo marks the onset of development. This process requires complex regulation to link developmental signals with profound changes in mRNA translation, cell cycle control, and metabolism. This control is beginning to be understood for most organisms, and research in the fruit fly Drosophila melanogaster has generated new insights. Recent findings have increased our understanding of the roles played by hormone and Ca2+ signaling events as well as metabolic remodeling crucial for this transition. Specialized features of the structure and assembly of the meiotic spindle have been identified. The changes in protein levels, mRNA translation, and polyadenylation that occur as the oocyte becomes an embryo have been identified together with key aspects of their regulation. Here we highlight these important developments and the insights they provide on the intricate regulation of this dramatic transition.